(untitled) - Greenblatt, Stephen (New York, 2004)
Interweaving a searching account of Elizabethan England with a vivid narrative of Shakespeare’s life, Greenblatt reveals in lively, accessible prose how an acutely sensitive and talented boy, surrounded by the rich tapestry of Elizabethan life-full of drama and pageantry, and also cruelty and danger-could have become the most important playwright of all time.
Keywords: Theater,Nhà hát; History,Lịch sử; 16th century.,Thế kỷ 16; England,Anh